How Balinese Culture Thrive on European Continent - Ida Bagus Putra Setiawan (Bali Tourism Board, 2022)
The Balinese workforce is one of the best workers with expertise in tourism, recognized by various companies engaged in hospitality services in different parts of the world. Along with the times, a few Balinese people migrated out of their homeland to pursue careers overseas. They spread to various corners of the world, especially to well-developed countries, for a better chance of living. Art and its strategic position in the Balinese Hindu community is the people’s expression of gratitude to the Higher being. As part of the religious activities of the Hindu community, a Ceremony or religious ritual held at the temple (holy place) always showcases performing arts. The customs are strongly associated with identity; for instance, despite being far away from Bali, the Balinese diaspora in Belgium commemorated Balinese Hindu holy days festively. In Pura Agung Santi Bhuana, Belgium, the Balinese Hindu Diaspora of Europe attended the temple ceremony in the early morning. The members of the social group Banjar performed their service by staging a dance and gamelan orchestra to accompany the holy day ceremony. The talented Balinese Diaspora on dance and play gamelan instruments constitute a significant part of the total population. They support the Government’s tourism promotion programs of the Republic of Indonesia through their traditional religious activities. Subsequently, they enlivened the existence of temples in Europe, such as in Belgium, Hamburg, and Berlin, with their stunning performing dance and percussion art service. Balinese Hindu community who lives in Europe could maintain steadfastness by respecting their own culture amidst the onslaught of a global culture. He admitted that global influence penetrated all practical activities and influenced all aspects of life. Albeit the unevaded facts, thousands of the Balinese diaspora and the local citizens respectfully attended the religious movement.